VOICES OF CONFIDENCE: AN EMPIRICAL AND LITERATURE REVIEW OF STUDENTS’ EXPERIENCES WITH SELF-EFFICACY IN WRITING - arifin, arifin (University of Muhammadiyah Malang, 2024)
This article discusses some writing difficulties faced by university students, and experts strategies to improve self-efficacy and the different aspects of self-efficacy in building students' confidence in writing. The purpose of this article is to provide a comprehensive overview of the word